Association of heart failure with procedural complications and in-hospital outcomes from left atrial appendage occlusion device implantation in patients with atrial fibrillation: insights from the national inpatient sample of 62 980 procedures . Issue 9 (25th May 2022) - Munir, Muhammad Bilal; Khan, Muhammad Zia; Darden, Douglas; Abideen Asad, Zain Ul; Osman, Mohammed; Singh, Gagan D; Srivatsa, Uma N; Han, Frederick T; Reeves, Ryan; Hsu, Jonathan C
Abstract: Aims: To determine outcomes in atrial fibrillation (AF) patients undergoing percutaneous left atrial appendage occlusion (LAAO) with concomitant heart failure with preserved ejection fraction (HFpEF) and heart failure with reduced ejection fraction (HFrEF). Methods and results: Data were extracted from National Inpatient Sample for calendar years 2015–2019. LAAO device implantations were identified on the basis of ICD-10-CM code of 02L73DK. The outcomes assessed in our study included complications, in-patient mortality, and resource utilization. A total of 62 980 LAAO device implantations were studied. HFpEF (14.4%, n = 9040) and HFrEF (11.2%, n = 7100) were associated with a higher prevalence of major complications and in-patient mortality in crude analysis. In the multivariate model adjusted for potential confounders, HFpEF and HFrEF were not associated with major complications [adjusted odds ratio (aOR) 1.04, 95% confidence interval (CI) 0.93–1.16 and aOR 1.07, 95% CI 0.95–1.21] or in-patient mortality (aOR 1.48, 95% CI 0.85–2.55 and aOR 1.26, 95% CI 0.67–2.38). HFpEF and HFrEF were associated with prolonged length of stay (LOS) > 1 day (aOR 1.41, 95% CI 1.31–1.53 and aOR 1.66, 95% CI 1.53–1.80) and increased hospitalization costs > median cost 24 752 (aOR 1.26, 95% CI 1.19–1.34 and aOR 1.21, 95% CI 1.13–1.29). Conclusion: The prevalence of HF in AF patients undergoing percutaneous LAAO was approximately 26%. HF was not independently associated with major complications and in-patient mortality but was associated with prolonged LOS and higher hospitalization costs.